Influence of Work Environment and Organizational Culture on Turnover Intention is Mediated by Job Satisfaction Type B Private Hospital in Bekasi - Desy Purwanti; Rhian Indradewa (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of the work environment, organizational culture on turnover intention mediated by job satisfaction at a type B private hospital in Bekasi. The design of this study uses a quantitative approach with data collection methods using questionnaires distributed online to health workers who are still actively working in hospitals as many as 275 respondents. Furthermore, the data analysis used in this study used SEM-PLS with the help of the SmartPLS software program. Data collection was carried out in December 2021 - January 2022. The results of this study indicate that the more conducive the work environment in type B Private Hospitals, the higher the job satisfaction of health workers, and a conducive work environment can also reduce the desire of health workers to change jobs. A strong organizational culture will reduce the desire to change jobs and high job satisfaction will reduce the desire of health workers to move from their current workplace.